Painful leg and missing pulses: a case report. Issue 4 (1st October 2000) - Chan, C W M; Wilson, J I; Myatt, A; Roberts, P N
Abstract : Popliteal artery entrapment syndrome (PAES) is a rare but potentially limb threatening anatomical anomaly occurring predominantly in young adults. We report a case of a 14 year old boy who presented with limb threatening ischaemia requiring urgent surgery. The pathology, presentation, and management are discussed.